Daniel visits the library - Testa, Maggie (Daniel Tiger's neighborhood., 2015)
"Daniel Tiger and Prince Wednesday are so excited for story time at the library! But first they have to learn how to be calm and quiet. Can they calm down before story time starts?" -- provided by publisher.